Effective Methods of Passing Examples of The Narrative Genre In Reading Lessons Based on Interactive Methods - SAPAYEVA, Layla; Roziyeva, M.Y. (International Journal on Integrated Education, 2023)
The article describes effective methods of passing examples of the narrative genre in reading lessons based on interactive methods. To achieve this goal, various forms of lessons – "Boomerang" technology, "Saw", "Find your place", "FSMU", "Why?", "Two– part diary" methods, , "Pinboard" method, the use of exercises such as "Recover the poem" increases the effectiveness of the lesson.